Constitutional Standards Regulating Administrative Function - Hussein Wali, Researcher.Mona; Majid Jasim, Assist.Prof.Batoul; Attwan Khalaf, Prof. Dr. Mohammed (Basra studies journal, 2024)
This research sheds light on the role of direct constitutional standards in regulating administrative functions, as administrative function is the legal tool for implementing the public policy of the state, and the monitoring tool for all administrative tasks. Therefore, many countries with established administrative principles focus on establishing legislative rules that clarify the ethics of this profession and its internal and external environment. What distinguishes this function is that it has undergone two concepts: the first with a personal nature involving waste of disciplinary guarantees, and the second with a legal nature granting the necessary guarantees and attention to the administrative function in various fields. This is achieved by identifying the most important direct constitutional standards that contribute to regulating administrative function, studying the implications of these standards on administrative organization, and identifying the main problems that hinder the application of these standards in organizing the function. We adopted the descriptive-analytical approach to the texts of the constitution that dealt with the organization of administrative function, to determine the extent of the legislator's interest in these standards and their establishment as a basis for implementing the state's public policy. We cited some advanced countries as examples of how the constitutional legislator clearly stated these standards, and the effectiveness of their application in reality. It turns out that the Constitution of the Republic of Iraq for the year 2005 did not regulate the administrative function, but Article (107) left the matter of organizing the function to the law, and in this regard, there is a clear shortcoming by the constitutional legislator. It is necessary to establish constitutional texts that include general principles for organizing the administrative function, so that the ordinary legislator can refer to them when organizing the function, and to ensure that he does not deviate in the use of this right granted to him by the constitutional legislator.